Renal function-based contrast dosing to define safe limits of radiographic contrast media in patients undergoing percutaneous coronary interventions - Gurm, Hitinder S; Dixon, Simon R; Smith, Dean E; Share, David; Lalonde, Thomas; Greenbaum, Adam; Moscucci, Mauro (Journal of the American College of Cardiology, 2011)
The aim of this study was to evaluate the association between calculated creatinine clearance (CCC)-based contrast dose and renal complications in patients undergoing percutaneous coronary interventions (PCI). Excess volumes of contrast media are associated with renal complications in patients undergoing cardiac procedures. Because contrast media are excreted by the kidney, we hypothesized that a dose estimation on the basis of CCC would provide a simple strategy to define a safe dose of contrast media. We assessed the association between CCC-based contrast dose and the risk of contrast-induced nephropathy (CIN) and need for in-hospital dialysis in 58,957 patients undergoing PCI and enrolled in the BMC2 (Blue Cross Blue Shield of Michigan Cardiovascular Consortium) registry from 2007 to 2008. Patients receiving dialysis at the time of the procedure were excluded. The risk of CIN and nephropathy requiring dialysis (NRD) was directly associated with increasing contrast volume adjusted for renal function. The risk for CIN and NRD approached significance when the ratio of contrast dose/CCC exceeded 2 (adjusted odds ratio [OR] for CIN: 1.16, 95% confidence interval [CI]: 0.98 to 1.37, adjusted OR for NRD: 1.72, 95% CI: 0.9 to 3.27) and was dramatically elevated in patients exceeding a contrast to CCC ratio of 3 (adjusted OR for CIN: 1.46, 95% CI: 1.27 to 1.66, adjusted OR for NRD: 1.89, 95% CI: 1.21 to 2.94). Our study supports the need for minimizing contrast dose in patients with renal dysfunction. A contrast dose on the basis of estimated renal function with a planned contrast volume restricted to less than thrice and preferably twice the CCC might be valuable in reducing the risk of CIN and NRD.